Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine how the function [tex]\( f(x) \)[/tex] was transformed to become [tex]\( g(x) \)[/tex], we need to analyze the given pairs of [tex]\((x, y)\)[/tex] points for both [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]. Let's compare the [tex]\( y \)[/tex]-values of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] for corresponding [tex]\( x \)[/tex]-values.
Given points:
- For [tex]\( x = -2 \)[/tex]:
[tex]\( f(-2) = \frac{1}{9} \)[/tex]
[tex]\( g(-2) = -\frac{17}{9} \)[/tex]
- For [tex]\( x = -1 \)[/tex]:
[tex]\( f(-1) = \frac{1}{3} \)[/tex]
[tex]\( g(-1) = -\frac{5}{3} \)[/tex]
- For [tex]\( x = 2 \)[/tex]:
[tex]\( f(2) = 9 \)[/tex]
[tex]\( g(2) = 7 \)[/tex]
- For [tex]\( x = 3 \)[/tex]:
[tex]\( f(3) = 27 \)[/tex]
[tex]\( g(3) = 25 \)[/tex]
- For [tex]\( x = 4 \)[/tex]:
[tex]\( f(4) = 81 \)[/tex]
[tex]\( g(4) = 79 \)[/tex]
From this, we can determine how [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] relate to each other for each point:
1. For [tex]\( x = -2 \)[/tex]:
[tex]\[ g(-2) = f(-2) - 2 \quad \Rightarrow \quad -\frac{17}{9} = \frac{1}{9} - 2 \][/tex]
2. For [tex]\( x = -1 \)[/tex]:
[tex]\[ g(-1) = f(-1) - 2 \quad \Rightarrow \quad -\frac{5}{3} = \frac{1}{3} - 2 \][/tex]
3. For [tex]\( x = 2 \)[/tex]:
[tex]\[ g(2) = f(2) - 2 \quad \Rightarrow \quad 7 = 9 - 2 \][/tex]
4. For [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = f(3) - 2 \quad \Rightarrow \quad 25 = 27 - 2 \][/tex]
5. For [tex]\( x = 4 \)[/tex]:
[tex]\[ g(4) = f(4) - 2 \quad \Rightarrow \quad 79 = 81 - 2 \][/tex]
It is clear from these calculations that for any [tex]\( x \)[/tex]:
[tex]\[ g(x) = f(x) - 2 \][/tex]
This describes a vertical shift of the parent function [tex]\( f(x) \)[/tex] downward by 2 units.
Therefore, the correct transformation is a vertical shift.
Thus, the correct answer is:
[tex]\[ \boxed{4 \text{ (Horizontal or vertical shift)}} \][/tex]
Given points:
- For [tex]\( x = -2 \)[/tex]:
[tex]\( f(-2) = \frac{1}{9} \)[/tex]
[tex]\( g(-2) = -\frac{17}{9} \)[/tex]
- For [tex]\( x = -1 \)[/tex]:
[tex]\( f(-1) = \frac{1}{3} \)[/tex]
[tex]\( g(-1) = -\frac{5}{3} \)[/tex]
- For [tex]\( x = 2 \)[/tex]:
[tex]\( f(2) = 9 \)[/tex]
[tex]\( g(2) = 7 \)[/tex]
- For [tex]\( x = 3 \)[/tex]:
[tex]\( f(3) = 27 \)[/tex]
[tex]\( g(3) = 25 \)[/tex]
- For [tex]\( x = 4 \)[/tex]:
[tex]\( f(4) = 81 \)[/tex]
[tex]\( g(4) = 79 \)[/tex]
From this, we can determine how [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] relate to each other for each point:
1. For [tex]\( x = -2 \)[/tex]:
[tex]\[ g(-2) = f(-2) - 2 \quad \Rightarrow \quad -\frac{17}{9} = \frac{1}{9} - 2 \][/tex]
2. For [tex]\( x = -1 \)[/tex]:
[tex]\[ g(-1) = f(-1) - 2 \quad \Rightarrow \quad -\frac{5}{3} = \frac{1}{3} - 2 \][/tex]
3. For [tex]\( x = 2 \)[/tex]:
[tex]\[ g(2) = f(2) - 2 \quad \Rightarrow \quad 7 = 9 - 2 \][/tex]
4. For [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = f(3) - 2 \quad \Rightarrow \quad 25 = 27 - 2 \][/tex]
5. For [tex]\( x = 4 \)[/tex]:
[tex]\[ g(4) = f(4) - 2 \quad \Rightarrow \quad 79 = 81 - 2 \][/tex]
It is clear from these calculations that for any [tex]\( x \)[/tex]:
[tex]\[ g(x) = f(x) - 2 \][/tex]
This describes a vertical shift of the parent function [tex]\( f(x) \)[/tex] downward by 2 units.
Therefore, the correct transformation is a vertical shift.
Thus, the correct answer is:
[tex]\[ \boxed{4 \text{ (Horizontal or vertical shift)}} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.